2019
DOI: 10.1016/j.envres.2019.108598
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional natural gas development and adverse birth outcomes in Pennsylvania: The potential mediating role of antenatal anxiety and depression

Abstract: Background: Studies have reported associations between unconventional natural gas development (UNGD) and adverse birth outcomes. None have evaluated potential mediating mechanisms. Objectives: To evaluate associations between (1) UNGD and antenatal anxiety and depression and (2) antenatal anxiety and depression and preterm birth (< 37 weeks gestation) and reduced term birth weight, (3) stochastic direct and indirect effects of UNGD on preterm birth and term birth weight operating through antenatal anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 105 publications
(153 reference statements)
0
12
0
Order By: Relevance
“…An increasing number of studies find that residents living near unconventional hydraulic fracturing sites suffer from poor mental health, including elevated levels of stress [ 2 , 4 , 6 , 16 , 17 , 19 ]. Nevertheless, additional research is needed, especially in countries other than the United States where findings may not be replicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies find that residents living near unconventional hydraulic fracturing sites suffer from poor mental health, including elevated levels of stress [ 2 , 4 , 6 , 16 , 17 , 19 ]. Nevertheless, additional research is needed, especially in countries other than the United States where findings may not be replicated.…”
Section: Discussionmentioning
confidence: 99%
“…Hydraulic fracturing that accompanies shale gas development is stressful because it is perceived to threaten physical health [ 4 , 19 , 20 ]. Brasier et al [ 2 ] (p. 38) learned that health experts in Pennsylvania were concerned about hydraulic fracturing and shale gas development, saying “we’ve done a number of assessments…there are some community perceptions that there are some health issues.” Fisher et al [ 19 ] also uncovered that residents in two Ohio (USA) counties that lived within 5 miles of hydraulic fracturing well faced considerable levels of stress due to their health concerns about those wells.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemiological studies that have used the proximity WA or similar models have all observed the greatest health implications in the densest areas of O&G well activity, generally at residences within 20 km of a well [2,[4][5][6][7][8][9][10][11][12][13][14][15]. McMullin et al (2018) recently evaluated air pollution measured from monitors at distances from O&G wells ranging from 0.1 km to 1.13 km to the closest O&G site and found a number of VOCs, notably benzene, ethylbenzene, and n-nonane [16].…”
Section: Distance Between Air Monitoring Sites and Wells: A Mismatch mentioning
confidence: 99%
“…In fact, the metric was designed to capture complex, multifactorial exposures, including air, water, noise, and light pollution as well as community disruption, psychosocial stress, increased traffic, and other potential impacts related to O&G activity [19]. Most prior epidemiologic studies note this [2,[4][5][6][7][8][9][10][11][12][13][14][15] and acknowledge the limitations of using a WA metric. Therefore, Hess et al have misinterpreted the purpose of the WA metric.…”
Section: Misrepresentation Of the Wa Metrics Used In Epidemiologic Stmentioning
confidence: 99%